Bear microsats for Paper For Dryad Archive - Cronin, Matthew A.; MacNeil, Michael D. (Dryad Digital Repository, 2012)
The file contains diploid genotypes for eight microsatellite DNA locifor three species of bears that were first reported in previous publications.